ОСОБЕННОСТИ РАССМОТРЕНИЯ ИСКОВ, ВЫТЕКАЮЩИХ ИЗ АДМИНИСТРАТИВНЫХ ОТНОШЕНИЙ - Сосна, Александр (SUPREMANCE OF LAW, 2016)
The author has attempted to provide an analysis of the laws governing the submission and consideration of claims arising out of administrative relations, the order of execution of the decisions of administrative courts, have entered into force, to draw attention to the controversial law, gaps in the law, legal regulations that impede protection of the rights of individuals and entities violated by illegal administrative acts, and to make proposals aimed at improving the legal rules governing the submission and consideration of claims arising out of administrative relations, as well as the order of execution entered into force decisions of the administrative courts.
Keywords: administrative relationships; claims; claim; administrative court